Simultaneous quantification of crocetin esters and picrocrocin changes in Chinese saffron by high-performance liquid chromatography-diode array detector during 15 years of storage - Tong, Yingpeng (Pharmacogn Mag, 2015)
BACKGROUND: Saffron, which is made up of the dried stigmas of Crocus sativus L., has been successfully cultivated in China since 1970s and Zhejiang province is now the largest producing area in China, but the contents of crocetin esters and picrocrocin in saffron from Zhejiang province has not been determined simultaneously by high-performance liquid chromatography (HPLC) and changes of these constituents in Chinese saffron during storage for years has not been studied. OBJECT: To establish a simple method quantification of the five main compounds including picrocrocin and four crocetin esters in saffron from main producing areas of China and study the influence of storage time on the changes of saffron constituents. MATERIALS AND METHODS: A simple, sensitive, and accurate HPLC method was developed for simultaneous determination of five major active components in saffron and eight samples which collected from the same farm of Zhejiang province in different years were analyzed. RESULTS: The correlation coefficient values (R(2) > 0.9997) indicated good correlations between the investigated compounds’ concentrations and their peak areas within the test ranges. The limits of quantification and detection of the five compounds were 0.53–2.76 μg/mL and 0.11–0.77 μg/mL, respectively. The recoveries ranged from 94.67% to 101.31%, and the overall relative standard deviations for intra-day and inter-day were lower than 3.49%. The method was applied to study the changes of crocetin esters and picrocrocin contents in saffron samples during 15 years of storage. The losses of crocetin esters and picrocrocin in saffron with 1 -year storage were 52.2% and 54.3%, respectively. The trend then declined during subsequent storage. CONCLUSION: The developed method can be applied to the intrinsic quality control of saffron.